2003
DOI: 10.1097/01.lab.0000053913.85892.e9
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profile of Serial Samples of Transformed B-Cell Lymphomas

Abstract: SUMMARY:Follicular lymphoma (FL) is characterized by a continuous rate of relapse and transformation to a high-grade lymphoma, usually diffuse large B-cell lymphoma (DLBCL), associated with a dismal prognosis and a poor response to conventional chemotherapy. The progression of indolent to aggressive FL is accompanied by the successive accumulation of recurrent chromosomal defects, but the resultant alterations of gene expression are largely unknown. To expand the understanding of the pathogenesis of FL transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
65
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(72 citation statements)
references
References 71 publications
7
65
0
Order By: Relevance
“…Interestingly, of their top list of 36 upregulated and 66 downregulated genes upon transformation, seven genes were also identified by Lossos et al 129 Among others, this involved increased expression of CDA and GAPD, two genes reflecting levels of metabolism, and decreased expression of the transcription factor IRF8 and of PTPRC (CD45). De Vos et al 130 also noted downregulation of different T-cell markers upon transformation such as CD7, FYB (Fyn binding protein) and SEMA4D (CD100). Elenitoba-Johnson et al 131 studied 11 FLs that transformed into DLBCL.…”
Section: Molecular Pathways In Follicular Lymphomamentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, of their top list of 36 upregulated and 66 downregulated genes upon transformation, seven genes were also identified by Lossos et al 129 Among others, this involved increased expression of CDA and GAPD, two genes reflecting levels of metabolism, and decreased expression of the transcription factor IRF8 and of PTPRC (CD45). De Vos et al 130 also noted downregulation of different T-cell markers upon transformation such as CD7, FYB (Fyn binding protein) and SEMA4D (CD100). Elenitoba-Johnson et al 131 studied 11 FLs that transformed into DLBCL.…”
Section: Molecular Pathways In Follicular Lymphomamentioning
confidence: 99%
“…132,133 Interestingly, it was shown that the CD4 þ CD25 þ FOX-P3 þ regulatory T cells also expressed high levels of CD7, which was one of the T-cell markers identified in the microarray studies. 127,130,134 In addition, the number of FOX-P3 þ regulatory T cells decreased dramatically in five FLs that underwent transformation into DLBCLs. 132 Regulatory T cells can either inhibit CD4 þ CD25 À T cells, including GC T cells, which may support FL B-cell proliferation/survival.…”
Section: Molecular Pathways In Follicular Lymphomamentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, high expression levels of Nek2 have been strongly associated with disease progression in non-Hodgkin lymphomas (38). Moreover, deregulation of Nek2 has been linked to centrosome abnormalities and aneuploidy.…”
Section: Bacterial Expression Of Nek2 Constructs and Phosphorylationmentioning
confidence: 99%